Private International Law in Mainland China, Taiwan and Europe - Pißler, Knut Benjamin; Basedow, Jürgen (Mohr Siebeck, 2014)
Over the last decades, private international law has become the target of intense codification efforts. Inspired by the stimulating initiatives taken by some European countries, by the Brussels Convention and the Rome Convention, numerous countries in other regions of the world started to enact comprehensive legislation in the field. Among them are Taiwan and mainland China. Both adopted statutes on private international law in 2010. In light of the rising significance of the mutual economic and societal relations between the jurisdictions involved and of the legal innovations laid down in the new instruments, the Max Planck Institute for Comparative and International Private Law convened scholars to present the conflict rules adopted in Europe, in mainland China and in Taiwan across a whole range of private law subjects. This book collects the papers of the conference and presents them to the public, together with English translations of the acts of Taiwan and mainland China.